Humidification Performance of Passive and Active Humidification Devices Within a Spontaneously Breathing Tracheostomized Cohort. - Nobuto Nakanishi; Jun Oto; Taiga Itagaki; Emiko Nakataki; Mutsuo Onodera; Masaji Nishimura (Respiratory Care, 2019)
BACKGROUND: Most heat-and-moisture exchangers (HMEs) for patients with tracheostomy and spontaneously breathing are small and have suction ports that allow some expiratory gas to escape, which loses vapor held in the expired gas. Recently, a heated-and-humidified high-flow system for spontaneously breathing patients with tracheostomy was developed. Little is known, however, about the humidifying performance of HMEs or heated-and-humidified high-flow systems for spontaneous breathing patients with a tracheostomy. OBJECTIVE: To investigate the humidifying performance of the HMEs and heated-and-humidified high-flow systems for spontaneously breathing patients with tracheostomy. METHODS: Adult spontaneously breathing subjects with tracheostomy and were enrolled when their respiratory parameters and ... were stable. We measured absolute humidity, relative humidity, and temperature by using a capacitance-type moisture sensor at the outlet of the tracheostomy tube. Heated-and-humidified high flow was delivered via the a humidifier and tracheostomy interface, and a selected HME. The subjects received heated-and-humidified high flow, after which an HME was used for humidification before switching back to a heated-and-humidified high-flow system. RESULTS: Ten subjects (5 men, 5 women; mean ± SD age, 72 ± 12 y) were enrolled. The admission diagnoses were neurologic (5 subjects), respiratory failure (3), and cardiac arrest (2). The APACHE (Acute Physiology and Chronic Health Evaluation) II score was 24 (interquartile range, 20-27). Tracheostomy was performed on day 7 (interquartile range, 5-11 d) after endotracheal intubation, and the duration of mechanical ventilation was 10 d (interquartile range, 6-11 d). The temperature with the HME was 29.9 ± 1.0°C and, during heated-and-humidified high-flow use was 35.3 ± 0.8°C (P < .001). With both the HME and the heated-and-humidified high-flow system, the relative humidity reached 100%; the absolute humidity with HME was 30.2 ± 1.8 mg/L, and, with the heated-and-humidified high-flow system, was 40.3 ± 1.8 mg/L (P < .001). CONCLUSIONS: In spontaneously breathing subjects with tracheostomy, an heated-and-humidified high-flow system achieved higher absolute humidity than did an HME.